A Study of History, Politics and Romance in Vikram Seth’s: Exploring the Transformation of English in Postcolonial India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present work examines the nativization procedure of English in India and in Indian English fiction, specifically, in the post frontier stage. Nativization extended the dialect, formed and refashioned it to such an extent that after this time it has its very own personality and place in the phonetic world. The obstruction against imperialistic attitudes towards build up close to home and additionally collective personalities in postcolonial India brought about a progression of changes to the English dialect. Subsequently, Indian English writers built up their claim sociological, semantic and abstract articulations.